Estimating the Endogenously Determined Intrahousehold Balance of Power and Its Impact on Expenditure Pattern : Evidence from Nepal - Koolwal, Gayatri; Ray, Ranjan (World Bank, Washington, D.C., 2013)
The collective approach to household behavior relaxes the restrictive features of the unitary model by specifying household welfare as a weighted combination of the individuals' utilities. But the weights are assumed fixed or exogenous to the analysis. The authors extend the collective approach by proposing and estimating a framework where the weights are determined and simultaneously estimated with the household outcomes. The authors present Nepalese evidence that suggests that a woman's share of household earnings understates her "power" in making household decisions. An increase in the woman's educational experience leads to a rise in her bargaining power. The results also reveal some interesting nonmonotonic relationships between a woman's "power" and the household's expenditure outcomes.